2016
DOI: 10.1016/j.envres.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Urinary concentrations of cyclohexane-1,2-dicarboxylic acid monohydroxy isononyl ester, a metabolite of the non-phthalate plasticizer di(isononyl)cyclohexane-1,2-dicarboxylate (DINCH), and markers of ovarian response among women attending a fertility center

Abstract: Di(isononyl)cyclohexane-1,2-dicarboxylate (DINCH), a non-phthalate plasticizer, was introduced commercially in 2002 as an alternative to ortho-phthalate esters because of its favorable toxicological profile. However, the potential health effects from DINCH exposure remain largely unknown. We explored the associations between urinary concentrations of metabolites of DINCH on markers of ovarian response among women undergoing in vitro fertilization (IVF) treatments. Between 2011 and 2015, 113 women enrolled a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 26 publications
(39 reference statements)
1
20
0
Order By: Relevance
“…Similarly, as research accumulates on the adverse health consequences of exposure to specific EDCs, substitute chemicals are introduced into the market such as bisphenol S and F, for BPA, and di-(iso-nonyl)-cyclohexane-1,2-dicarboxylate (DINCH), for high molecular weight phthalates. Thus, while exposure to certain EDCs such as BPA and DEHP may be declining, exposure to many others are on the rise [25, 49] and early studies suggest they may not be safer alternatives [50, 51]. Future research should focus on incorporating the assessment of these newer chemicals into ongoing studies to assess the potential effects that these chemicals could have on human fecundity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, as research accumulates on the adverse health consequences of exposure to specific EDCs, substitute chemicals are introduced into the market such as bisphenol S and F, for BPA, and di-(iso-nonyl)-cyclohexane-1,2-dicarboxylate (DINCH), for high molecular weight phthalates. Thus, while exposure to certain EDCs such as BPA and DEHP may be declining, exposure to many others are on the rise [25, 49] and early studies suggest they may not be safer alternatives [50, 51]. Future research should focus on incorporating the assessment of these newer chemicals into ongoing studies to assess the potential effects that these chemicals could have on human fecundity.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Human exposure to phthalates is ubiquitous in the United States, Europe, and elsewhere. [26][27][28] Regulation of some phthalates has prompted the use of plasticizer replacement chemicals such as 1,2-cyclohexane dicarboxylic acid diisononyl ester (DINCH). Substitution of phthalates with DINCH warrants further screening in human populations 29 because its metabolites are biologically active and understudied.…”
Section: Introductionmentioning
confidence: 99%
“…di-2-ethylhexyl phthalate (DEHP) in children's toys] have been replaced by 1,2 cyclohexane dicarboxylic acid, diisononyl ester (DINCH) (Silva et al, 2013). Little is known about the potential human health effects of DINCH exposure but recent studies have reported that a metabolite of DINCH, cyclohexane-1,2-dicarboxylic acid monoisonyl ester (MHINCH), may interfere with the endocrine system in animal models (Campioli et al, 2015), and may alter female reproductive health in ways that are similar to DEHP (Minguez-Alarcon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%